2022
DOI: 10.7717/peerj.13852
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing network pharmacology and experimental validation to investigate the underlying mechanism of phellodendrine on inflammation

Abstract: Background Phellodendrine, one of the characteristic and important active components of Cortex phellodendri, has been proven to show anti-inflammatory effects. However, the underlying mechanism of phellodendrine on inflammation remains largely unclear. Aim of the study In this study, network pharmacology and experimental validation were used to explore the underlying mechanism of phellodendrine on inflammation. Materials and Methods PubChem and SwissADME database were used to evaluate the drug-likeness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Rutin promoted SOD2 , LC3 and BAX , and inhibited ULK2 , CAS3 and CAS9 , which is consistent with reports stating that it enhances the expression of antioxidant enzymes (e.g., SOD , CAT , GPX ) and inhibits the expression of apoptotic genes such as CAS3 , CAS7 , CAS9 , and P53 [ 26 , 30 ]. Phellodendrine promoted SOD1 , SOD2 , ATG3 and LC3 , and inhibited CAS3 and CAS9 , which is consistent with reports of it regulating the AMPK/mTOR pathway, reducing PTGS1 , PTGS2 , AKT phosphorylation, and NF-kB3, and having autophagy, anti-inflammatory, and antioxidant effects [ 31 , 32 , 33 ]. All three compounds promoted the expression of oxidative stress-related genes, reduced the accumulation of intracellular ROS, inhibited the expression of apoptotic genes, reduced mitochondrial damage, promoted polar body emissions, and inhibited cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Rutin promoted SOD2 , LC3 and BAX , and inhibited ULK2 , CAS3 and CAS9 , which is consistent with reports stating that it enhances the expression of antioxidant enzymes (e.g., SOD , CAT , GPX ) and inhibits the expression of apoptotic genes such as CAS3 , CAS7 , CAS9 , and P53 [ 26 , 30 ]. Phellodendrine promoted SOD1 , SOD2 , ATG3 and LC3 , and inhibited CAS3 and CAS9 , which is consistent with reports of it regulating the AMPK/mTOR pathway, reducing PTGS1 , PTGS2 , AKT phosphorylation, and NF-kB3, and having autophagy, anti-inflammatory, and antioxidant effects [ 31 , 32 , 33 ]. All three compounds promoted the expression of oxidative stress-related genes, reduced the accumulation of intracellular ROS, inhibited the expression of apoptotic genes, reduced mitochondrial damage, promoted polar body emissions, and inhibited cell apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous studies have shown that SKHS contains various potential natural compounds, such as phellodendrine and obacunone, 17) that exhibit antibacterial or anti-inflammatory effects. 41,42) Molecular docking studies have elucidated that both phellodendrine and obacunone, components found in SKHS, exhibit robust binding affinity with ptpA. However, their binding affinity with arlR_1 appears to be relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, for example, baicalein, baicalin, wogonin, wogonoside, oroxylin A, and scutellarin, show anti-inflammatory activity [29,30], and baicalin also shows an antipyretic effect [31]. Alkaloids, for example, phellodendrine and berberine, show anti-inflammatory activity [32,33], and indigo and indirubin show antioxidant activity [34]. Terpenoids, for example, geniposidic acid, protects LPS-induced ALI through the TLR4/MyD88 signaling pathway [35], and geniposide, genipin, and crocin-I show anti-inflammatory activity [36][37][38].…”
Section: Characterization and Identification Of Alkaloidsmentioning
confidence: 99%